Internet banking adoption in Indonesia: TAM extention with the moderation role of customer knowledge and trust - Yudi Sutarso; Djoko Budi Setyawan (Jurnal Manajemen dan Pemasaran Jasa, 2022)
This study examines the role of customer knowledge and trust in the technology acceptance model (TAM) on internet banking (IB) in Indonesia. It proposes a hypothesis that customer knowledge and trust moderate the relationship between perceived usefulness and ease of use with attitudes toward IB, which in turn, it can also influence intention to use IB. The sample was taken by purposive sampling technique from the customers of the three largest banks in Indonesia, namely Bank Mandiri, Bank Central Asia (BCA), and Bank Rakyat Indonesia (BRI). There were 280 respondents from these banks, and the data were analyzed by using the Structural Equation Model with the Partial Least Square approach. The significant finding in this study is that customer knowledge moderates positively the relationship between perceived ease of use and usefulness with customers’ attitudes. In addition, trust moderates negatively the relationship between perceived usefulness and attitudes toward IB. These findings extend the TAM model by adding the moderating role of customer knowledge and trust to the bank and recommend managers to increase customer adoption of IB.